The value of trabectedin in the treatment of soft tissue sarcoma - Nakamura T; Matsumine A; Sudo A (Dove Medical Press, 2016)
Tomoki Nakamura, Akihiko Matsumine, Akihiro Sudo Department of Orthopaedic Surgery, Mie University Graduate School of Medicine, Mie, Japan Abstract: Soft tissue sarcomas (STSs) are a group of rare tumors accounting for less than 1% of all adult malignant tumors, a heterogeneous group of more than 50 histological subtypes. Five percent to 30% of STS patients experience local recurrence and 10%–38% present with clinically detectable metastases. Doxorubicin either alone or in combination with ifosfamide has been used as first-line chemotherapy for advanced disease. After failure of first-line chemotherapy, high-dose ifosfamide, gemcitabine + docetaxel, and dacarbazine may be applicable, although high-level evidence is lacking. Trabectedin is a synthetic, marine-derived alkylating agent derived from the Caribbean tunicate, Ecteinascidia turbinata. Several clinical trials have shown that trabectedin has a favorable toxicity profile and is an alternative therapeutic option in adult patients with advanced STS who have not responded to treatment with doxorubicin and ifosfamide. Several clinical trials also recommend the 24-hour intravenous infusion every 3 weeks regimen. The most frequently reported grade 3/4 adverse events were neutropenia and elevated serum levels of AST/ALT. Steroid pretreatment is an effective way of reducing the extent of hepatotoxicity, and steroids are now given routinely before trabectedin administration. Further studies are ongoing to evaluate the efficacy and safety of combination therapy of trabectedin with other agents. Keywords: trabectedin, soft tissue sarcoma, efficacy, safety